Requirements for Beneficial Electrochemical Restructuring: A Model Study on a Cobalt Oxide in Selected Electrolytes. Issue 36 (7th August 2021) - Villalobos, Javier; González‐Flores, Diego; Urcuyo, Roberto; Montero, Mavis L.; Schuck, Götz; Beyer, Paul; Risch, Marcel
Abstract: The requirements for beneficial materials restructuring into a higher performance oxygen evolution reaction (OER) electrocatalyst are still a largely open question. Here erythrite (Co3 (AsO4 )2 ·8H2 O) is used as a Co‐based OER electrocatalyst to evaluate its catalytic properties during in situ restructuring into an amorphous Co‐based catalyst in four different electrolytes at pH 7. Using diffraction, microscopy, and spectroscopy, a strong effect in the restructuring behavior is observed depending of the anions in the electrolyte. Only carbonate electrolyte can activate the catalyst material, which is related to its slow restructuring process. While the catalyst turnover frequency (TOF) undesirably reduces by a factor of 28, the number of redox active sites continuously increases to a factor of 56, which results in an overall twofold increase in current of the restructured catalyst after 800 cycles. The activation is attributed to an adequate local order, a high Co oxidation state close to 3+, and a high number of redox‐active Co ions. These three requirements for beneficial restructuring provide new insights into the rational design of high‐performance OER catalysts by electrochemical restructuring. Abstract : The requirements of beneficial material restructuring into a high‐performance oxygen evolution reaction (OER) electrocatalyst are investigated. The nature of the anions in the electrolyte directly affects the restructuring kinetics. Only carbonate can activate the catalytic current, forming a final material with adequate local structure, high Co valence, and high redox activity that results in best performance.